Infant Physical Activity as A Strategy to Support Early Growth and Development: A Simple Observation Study - Nidya Comdeca Nurvitriana; Vina Firmanty Mustofa; Meifina Wildatul Firdauzi; Fika Churun Aini; Jamila; Tarisa Ramadhani (Faculty of Medicine, Universitas Negeri Surabaya, 2026)
Infants age 0-11 months are in a critical period of rapid growth and development known as the golde age. Proper stimulation, particularly physical activity, plays an important role in supporting optimal motor, sensory, and cognitive development. This study aims to describe the implementation of infant physical exercise as an early simulation strategy to support growth and development outcomes. A descriptive observation method was used and conducted in three different locations. Data were collected through direct observation, documentation, and interviews with parents and midwives. The results showed that infants with prior exposure to physical exercise were more comfortable, calm, and cooperative, while those without prior experience tended to be fussy and less adaptive. In addition, the sequence of activities and infant readiness influenced the effectiveness of stimulation. Baby spa, including baby gym, gym ball exercises, and baby massage, was found to be an effective approach to support infant growth and development. In conclusion, physical stimulation should be introduced early, gradually, and adjusted to the infant’s condition to achieve optimal developmental outcomes.